Agreement and reproducibility of field and laboratory tests in the prediction of running speed in a 10-km race in amateur runners - Ribeiro, Heitor Siqueira (Array, 2020)
Knowing running speed, particularly by means of easy-to-apply tests and low cost, is important for the definition of the race strategy and the most appropriate training throughout the preparation period. The aim was to compare the agreement and reproducibility of critical velocity (CV), anaerobic threshold (AT), and the simulated time trial on the track for the determination of the running speed in a 10-km race in amateur runners. A cross-sectional study was conducted with 34 runners of both genders aged 42.4±11.0 years. We measured their CV, assessed their body composition and AT. Participants performed also a simulated time trial on a 10-km running track and an official 10-km race. The delta of the comparisons and the standard error of estimate between the running velocities determined by the CV, AT, and the simulated time trial on the track ranged from 0.55 to -0.79 km/h and 0.14 to 0.59 km/h, respectively. Furthermore, CV and AT were compared to the 10-km running speed. Good agreement and reproducibility were observed between the velocities determined by the CV, AT, and the simulated time trial on the track with the real-time of a 10-km official race.